Labour Market Integration of Refugee Health Professionals in Germany: Challenges and Strategies - Sidra Khan-Gökkaya; Mike Mösko (International Migration, 2021)
Refugee health professionals are a vulnerable group in a host country's labour market as they experience several barriers on their path to labour market integration. This study aims to identify challenges refugee health professionals and their supervisors experience at their workplaces and strategies they have developed to overcome these barriers. Semi-structured interviews were conducted with refugee health professionals who have been living in Germany for an average of four years and their supervisors (n~=~24). The interviews were analysed using qualitative content analysis. Nine themes were identified: (1) recognition of qualifications, (2) language competencies, (3) differing healthcare systems, (4) working culture, (5) challenges with patients, (6) challenges with team members, (7) emotional challenges, (8) discrimination and (9) exploitation. Results indicate the need to implement structural changes in order to improve the labour market experiences of refugee health professionals.
Keywords: 300